Deficiency in the α1 subunit of Naa+/K+‐ARPase enhances the anti‐proliferative effect of high osmolality in nucleus pulposus intervertebral disc cells. Issue 12 (24th August 2015) - Mavrogonatou, Eleni; Papadimitriou, Konstantinos; Urban, Jill P.; Papadopoulos, Vassilios; Kletsas, Dimitris
<x xml:space="preserve">Abstract</x> Intervertebral disc cells are constantly exposed to a hyperosmotic environment. Among cellular responses towards this stress is the inhibition of proliferation through the activation of p38 MAPK and p53. In an effort to further elucidate the biochemical pathways triggered by hyperosmotic stress, we assessed the high osmolality‐induced transcriptional changes of bovine nucleus pulposus cells using whole‐genome arrays. A 5‐ and a 24‐h hyperosmotic treatment led to the differential expression of >100 and >200 genes, respectively, including nine genes encoding transporters (SLC4A11, SLC5A3, ATP1A1, SLC38A2, KCNK17, KCTD20, KCTD11, SLC7A5, and CLCA2). Differences in the transcriptional profile of these selected genes, as indicated by the microarrays experiments, were validated by qRT‐PCR in 2D and 3D cell cultures, under hyperosmolar salt and sorbitol conditions, revealing the presence of a common triggering signal for osmotic adaptation. The key signaling molecules p38 MAPK and p53 were demonstrated to differently participate in the regulation of the aforementioned transporters. Finally, siRNA‐mediated knocking‐down of each one of the three transporters with the highest and sustained over‐expression (i.e., SLC4A11, SLC5A3, and ATP1A1) had a distinct outcome on the transcriptional profile of the other transporters, on p38 MAPK and p53 phosphorylation and consequently on cell cycle progression. The inhibition of ATP1A1 had the most prominent effect on the transcription of the rest of the transporters and was found to enhance the anti‐proliferative effect of hyperosmotic conditions through an increased G2/M cell cycle block, ascribing to this pump a central role in the osmoregulatory response of nucleus pulposus cells. J. Cell. Physiol. 230: 3037–3048, 2015. © 2015 Wiley Periodicals, Inc.